Project Citizen and Resistance to Independent Waste Villages: A Case-Based Learning Approach in Matesih, Indonesia - Peni Kunthi Hermawati; Dewi Gunawati; Muhammad Hendri Nuryadi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Project Citizen can connect Civic Education with authentic public issues by engaging students in evidence-based inquiry and policy problem-solving. This study examined its implementation through a case-based learning approach using community resistance to the Independent Waste Village Program in Matesih, Indonesia, as the central civic issue. A descriptive qualitative case-study design was employed involving senior high school students who participated in classroom discussions, field observations, stakeholder interviews, collaborative analysis, portfolio development, and policy presentations. Data were collected through observations, semi-structured interviews, student learning artefacts, and contextual information from community stakeholders. The data were analyzed thematically through coding, categorization, and comparison across data sources. Students identified several forms of resistance, including non-participation, token compliance, fee avoidance, alternative waste disposal, public skepticism, and uneven participation across neighborhoods. They interpreted these responses as being influenced by service unreliability, economic considerations, limited communication, perceived unfairness, and public distrust. The learning process supported the development of civic knowledge, inquiry, communication, collaboration, evidence-based reasoning, environmental responsibility, empathy, and policy advocacy. The findings indicate that community resistance can serve as a meaningful case for contextual Civic Education because it enables students to examine complex relationships among citizen responsibility, institutional performance, and public trust. However, the study was limited by its single-case qualitative design and the absence of standardized measures of competency development. Future studies should use broader samples, comparative designs, and validated assessment instruments.